The Effect of Static Core Training on Dynamic Balance in Football Games in Athletes of Palangga Gowa Football School - Bismar, Ahmad Rum; Nawir, Nukhrawi (Journal of Sport Education, Coaching, and Health (JOCCA), 2024)
This study aimed to examine the effect of static core training on dynamic balance in football athletes at Palangga Gowa Football School. A quasi-experimental design with a pretest-posttest control group was employed involving 30 male athletes aged 13–16 years. Participants were randomly assigned into two groups: an experimental group (n = 15) undergoing a 6-week static core training program and a control group (n = 15) continuing regular football training without additional core exercises. Dynamic balance was assessed using the Y-Balance Test before and after the intervention. Results showed a significant improvement in dynamic balance within the experimental group, with mean scores increasing from 72.5 ± 5.2 to 85.3 ± 4.8 (p < 0.001). In contrast, the control group exhibited a non-significant change, from 71.8 ± 6.0 to 74.1 ± 5.9 (p = 0.15). The independent sample t-test revealed a significant difference in post-test scores between groups (t = 6.12, df = 28, p < 0.001), indicating that static core training effectively enhances dynamic balance beyond standard training. These findings suggest that integrating static core exercises into youth football training programs may improve athletes’ postural stability and functional performance, potentially reducing injury risk. The study supports the adoption of targeted core conditioning as a strategic approach to optimize athletic development in football.